Chaos in the Liberal Order The Trump Presidency and International Politics in the Twenty-First Century - Jervis, Robert 1940-2021 (Columbia University Press, 2018)
Donald Trump's election has called into question many fundamental assumptions about politics and society. Collecting a wide range of perspectives from leading scholars, Chaos in the Liberal Order explores the global trends that led to Trump's stunning victory and the impact his presidency will have on the international political landscape